Improving Association Studies and Genomic Predictions for Climbing Beans With Data From Bush Bean Populations - Keller, Beat; Ariza-Suarez, Daniel; Portilla-Benavides, Ana Elisabeth; Buendia, Hector Fabio; Aparicio, Johan Steven; Amongi, Winnyfred; Mbiu, Julius; Msolla, Susan Nchimbi; Miklas, Phillip; Porch, Timothy G.; Burridge, James; Mukankusi, Clare; et al. (Frontiers in Plant Science, 2022)
Common bean (Phaseolus vulgaris L.) has two major origins of domestication, Andean and Mesoamerican, which contribute to the high diversity of growth type, pod and seed characteristics. The climbing growth types are associated with increased days to flowering (DF), seed iron concentration (SdFe), nitrogen fixation and yield. However, breeding efforts in climbing beans have been limited and independent from the breeding of bush type beans. To advance climbing bean breeding, we carried out genome-wide association studies and genomic predictions using over 1,800 common bean lines belonging to five breeding panels representing both gene pools and all growth types. The phenotypic data were collected from 16 field trials and were complemented with 16 previously published trials. Overall, 38 QTL affecting growth habit, 14 for DF, 13 for 100 seed weight, three for SdFe and one for yield were identified. Except for DF, the results suggest a common genetic basis for traits across all panels and growth types. Seven QTL associated with growth habit were confirmed from earlier studies and four plausible candidate genes for SdFe and 100 seed weight were newly identified. Furthermore, the genomic prediction for climbing beans for SdFe and yield improved up to 8.8% when bush type bean lines were included in the training population. In conclusion, a large breeding population from different gene pools and growth types across multiple breeding panels increased the power of genomic analysis and provides a solid and diverse germplasm base for genetic improvement of common bean.